PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERATIF TIPE THINK PAIR SHARE MELALUI PENYAJIAN MASALAH KONTEKSTUAL TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Fatmawati, Any (Bioscientist : Jurnal Ilmiah Biologi, 2013)
This study aims to create a model of learning devices at the elementary level by using cooperative learning type think pair share through the provision of contextual questions to train creative thinking skills and student learning outcomes. The method used is reference study, observation and experiment. Referral studies conducted are to study theories about the concept and structure of learning tools, cooperative learning model type think pair share, contextual questions and indicators of creative thinking skills at elementary school level. Furthermore, the observations made were to assess the learning tools commonly used by elementary school teachers, analysis of learning support resources, the context of IPA SD, the learning process undertaken by the teacher and the characteristics of the students. Experiments are used to get data about differences in the use of instructional devices in experiment and control classes. The results obtained from referral and observation studies will be a draft of modeling of cooperative learning tools of type think pair share through contextual questions. The results showed that first for the syllabus and RPP components there was no difference between the ones compiled by the researchers and those prepared by SDN 21 Ampenan teachers. However, there are some differences in preparing the RPP, firstly in terms of the material description, both in terms of number of meetings and, thirdly in terms of core activities (exploration, elaboration, and confirmation). Secondly, there is a relationship between the development of the model of cooperative learning type of think pair share through the presentation of contextual problems to the creative thinking skill of SDN 21 Ampenan students. Third, there is a relationship between the development of the model of cooperative learning type of think pair share through the presentation of contextual problems on student learning outcomes SDN 21 Ampenan. Fourth, there is a difference between the ability of creative thinking and learning outcomes between students who follow cooperative learning type think pair share through the presentation of contextual problems with students who follow the lecture learning.